Early diagnosis of airways obstruction - Cochrane, G. M. (1974)
Cochcrane, G. M., Prieto, F., Hickey, B., Benatar, S. R., and Clark, T. J. H.Thorax, 29, 389-393. Early diagnosis of airways obstruction. Three simple tests, maximum expiratory flow volume curve, maximum expiratory volume time curve and `closing volume', were used to detect early airways obstruction in 21 smokers. A high proportion had abnormal values for MEF(75%), MEF(50%), and FET (86%, 71%, and 62% respectively) with a relatively normal FEV(1). There was a good correlation between tests of small airways obstruction obtained from the forced expiratory manoeuvre. The measurement of `closing volume' (phase 4/VC%) was less satisfactory as there were difficulties with interpretation of the records in half of the studies. We conclude that the forced expiratory manoeuvre can be used to detect early airways obstruction as well as providing FEV(1) and vital capacity. The importance of early diagnosis of airways obstruction is not yet clear and further information is required about its natural history, and its relation to smoking habits and to the more advanced and less reversible stages of airways obstruction. It may be possible to use early detection to prevent the development of disabling chronic obstructive bronchitis.